Application of graphdiyne for promote efficient photocatalytic hydrogen evolution - Tian Wang; Zhiliang Jin (Results in Surfaces and Interfaces, 2024)
The photocatalytic hydrogen evolution technology converts solar energy into clean and environmentally friendly hydrogen energy, which is considered an effective means to solve environmental pollution and energy crisis. The unique sp and sp2 hybrid carbon network structure of graphdiyne endows it with excellent carrier mobility, and high porosity, making it a promising photocatalytic material for solar energy conversion. This article provides a detailed description of the unique structural properties and adjustable bandgap of graphdiyne. In addition, a detailed review was provided on the modification strategies of graphdiyne based catalysts for photocatalytic hydrogen evolution, including titanium based photocatalysts, metal oxide photocatalysts, double hydroxide catalysts, metal organic framework photocatalysts and other typical semiconductors. Finally, the challenges and opportunities for developing graphdiyne semiconductors for photocatalytic water splitting were proposed. Timely review is expected to contribute to the rapid development of graphdiyne in the field of photocatalytic hydrogen evolution.